Identification of Manganese Distribution Using Very Low Frequency (VLF) Method at Karangsari Village, Pengasih Sub-District, Kulonprogo Regency, DIY - Listyorini, Wulan; Niyartama, Thaqibul Fikri; Zakaria, Muhammad Faizal (Proceeding International Conference on Science and Engineering, 2017)
Research of manganese distribution was conducted in the village of Karangsari, Pengasih sub-district, Kulonprogo Regency, DIY which is the former area exploration and exploitation of manganese. The purpose of the research is known the value of relative conductivity and the distribution of manganese. The method used very low frequency tilt mode. The tools used 2 set of T-VLF BRGM (sensor and monitor) and the data processing software are Ms. Excel and KHFILT. T-VLF operated with 2 frequencies that are 19800 Hz from Australia and 22.200 Hz from Elbino Japan. The total lines are 6 lines with 75 m space. Distance between measured points is 15 m, whereas line length is 300 m. The parameters measured from VLF method are tilt (%) and ellipticity (%). The raw data VLF is processed by Ms Excel to obtain a tilt, ellipse, fraser graph vs distance and the RAE from Karous Hjelt filter. While the results of processed by KHFILT software is the equivalent current density contour map. Relative conductivity of area research are line 1 (-10 to 10) mho/m, line 2 (-40 to 30) mho/m, line 3 (-20 to 20) mho/m, line 4 (-30 to 10) mho/m, line 5 (-40 to 30) mho/m and line 6 (-30 to 40) mho/m. The spread of manganese were in the high conductivity, toward west and east of research area with depth up to 45 m.